mRNA in situ hybridization analysis of p-53 cancer suppression gene and Bcl-2 oncogene in chronic lymphocytic leukemia - Jaafar, Abdulkareem M.; Al-Rubaie, Haythem A.; Mustafa, Saad A.; Abbas Abdul Majeed, Ban (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Several factors render chronic lymphocytic leukemia (CLL) an interesting subject for study by researchers. These include marked progress in understanding the molecular biology of normal and neoplastic lymphocytes and recent advances in molecular genetics techniques. Among molecular markers, p53 cancer suppressor gene and the antiapoptotic gene Bcl-2 have been widely studied. Patients and methods: A retrospective cross-sectional study done on 60 patients with chronic lymphocytic leukemia compared with 20 controls (anemic patients), all recruited at the Medical City Teaching Hospital laboratories from January 2004 to December 2007. The bone marrow biopsy of each was re-examined histologically. In situ hybridization was performed utilizing biotin labeled p53 and Bcl-2 cDNA probes.Results: The frequency of p53 positive signals in the study group was 28.3% (17of 60 cases). A significantly larger number of patients, with high score for p53 signal, were associated with high-risk clinical stage than patients with low score (p = 0.005). There was a significant direct positive correlation between increasing scores of p53-positive chronic lymphocytic leukemia cells and advancing clinical stage of the disease (p =0.002). The frequency of Bcl-2 positivity was 50% (30 of 60 cases). No significant correlations found between Bcl-2 scores and clinical stage of the disease.Conclusion: Although p53 alteration may occur early in the course of the disease, as shown by the p53 positivity in a proportion of patients in low and intermediate-risk stage of the disease, the highest frequency p53-positive cells, has been observed in high-risk stage of the disease. Therefore, p-53 score is an important prognostic variable in patients with chronic lymphocytic leukemia. However, Bcl-2, as assessed by ISH, is not regarded as an important prognostic marker.